2016
DOI: 10.1111/jzo.12362
|View full text |Cite
|
Sign up to set email alerts
|

Territory selection in the city: can birds reliably judge territory quality in a novel urban environment?

Abstract: Although territory selection is likely to be under strong natural selection, in many cases it might be impossible for individuals to judge territory quality directly in terms of fitness return. Thus, animals often rely on some indirect environmental cues in territory assessment and they may not be able to make optimal settlement decisions when subjected to a novel environment. The aim of this study was to investigate adaptiveness of territory selection in a newly established urban population (Ł od z, central P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our previous studies in the Eurasian coot indicated that urban individuals are more willing to exploit novel anthropogenic food sources and show elevated boldness towards humans when compared with nonurban conspecifics (Minias et al, 2018 ). We also found a significant positive relationship between territory occupancy and reproductive success in urban coots, suggesting that they may have capabilities to reliably assess territory quality in a novel urban environment (Minias & Janiszewski, 2016 ). These patterns should likely be attributed to better cognition and exploratory behaviour, which may be linked to genetic differences in the expression of key behavioural genes.…”
Section: Discussionmentioning
confidence: 72%
“…Our previous studies in the Eurasian coot indicated that urban individuals are more willing to exploit novel anthropogenic food sources and show elevated boldness towards humans when compared with nonurban conspecifics (Minias et al, 2018 ). We also found a significant positive relationship between territory occupancy and reproductive success in urban coots, suggesting that they may have capabilities to reliably assess territory quality in a novel urban environment (Minias & Janiszewski, 2016 ). These patterns should likely be attributed to better cognition and exploratory behaviour, which may be linked to genetic differences in the expression of key behavioural genes.…”
Section: Discussionmentioning
confidence: 72%
“…Vegetation structure has implications for the suitability of a site for nest placement (Barati et al, 2011 ; Koivula & Rönkä, 1998 ), and influences probability of a territory being occupied (Minias & Janiszewski, 2016 )…”
Section: Synthesis Of Reviewed Studiesmentioning
confidence: 99%
“…Hemoglobin concentration does not correlate with breeding territory settlement decisions in terms of a territory's expected reproductive output (Minias & Janiszewski, 2016 )…”
Section: Synthesis Of Reviewed Studiesmentioning
confidence: 99%
“…Also, the successful urban colonizer must adopt or express substantial behavioral plasticity to different habitat structures and the density of the human population in towns [5,8,9]. Although many studies have analyzed the urbanization process, much less is understood about how animal populations differ in habitat requirements between urban and rural areas and how this difference mediates the behavior of animals [8,[10][11][12][13][14]. The selection of sites by animals to meet their requirements is a behavioral process itself; however, it is more related to physical components of the environment rather than any other types of behavior linked with the presence of conspecifics or different species (e.g., aggressive behavior or flocking).…”
Section: Introductionmentioning
confidence: 99%